Design and Implementation of Airborne Network Switch System Software Based on Fiber Channel Protocol - Wang, Kuisheng; He, Yikang (2024 9th International Conference on Intelligent Computing and Signal Processing (ICSP), 2024)
With the rapid development of information technology, network communication technology plays an increasingly important role in modern society. In data centers, enterprise networks and specific areas of communication needs, the performance and reliability of switches, as core equipment, are crucial. Fiber optic switches, as an advanced network device, are becoming the preferred choice due to its advantages of high speed, low latency and security. Fiber optic transmission is not subject to electromagnetic interference and has higher data security, making it suitable for sensitive areas such as finance and health care. In the aerospace field, the lightweight and anti-interference characteristics of fiber optic switches make them the first choice for airborne switches. This thesis will explore the principles, characteristics and applications of FC airborne network switches to support their promotion and application.